Platelet concentrates for revitalization of immature necrotic teeth: a systematic review of the clinical studies. (3rd July 2016) - Lolato, Alessandra; Bucchi, Cristina; Taschieri, Silvio; Kabbaney, Ahmed El; Fabbro, Massimo Del
Abstract: This systematic review aimed at determining the effectiveness of autologous platelet concentrate (APC) in the treatment of immature necrotic teeth. An electronic search was performed on MEDLINE, Embase, Scopus, SciELO, Lilacs, CENTRAL. Comparative clinical studies were included, in which APC was tested for pulp regeneration and radicular development. Selected articles underwent risk-of-bias assessment. Clinical and radiographic outcomes were considered. Three randomized parallel studies and one split-mouth case series were included. One study had low risk of bias and three studies had high risk. A total of 61 immature necrotic teeth were treated in 56 patients. Follow-up ranged between 12 and 18 months. All studies used platelet-rich plasma (PRP) in the test group, and one also used platelet-rich fibrin (PRF). After treatment, all teeth of control and experimental groups remained asymptomatic for the entire study duration. Only one study reported response to cold and electric pulp test, showing not significantly better outcomes for the test group. Similarly, periapical healing and apical closure were improved in the group treated with APC although statistical significance was not achieved ( P = 0.08 and P = 0.06, respectively), probably due to the limited sample size. The teeth treated with PRP achieved significantly better thickening of the dentin walls ( P = 0.01), and root lengthening ( P = 0.001) than control teeth. Despite the potential effectiveness of APC in promoting root development of necrotic immature teeth, scarce evidence exists regarding this subject. In the studies evaluated in this review, platelet concentrates showed promising results that warrant further investigation.